Difference In Knowledge About Stunting Among Families with Stunted Children and Non-Stunted Children in Labuhan Haji Village, East Lombok - Sesariana, Mayumi Agestia; Djannah, Fathul; Cahyawati, Triana Dyah; Restuningdyah, Novia Andansari Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Stunting is a condition characterized by a child's height or length being below the predicted range for their age, defined by a z-score of ≤2 SD in accordance with WHO child growth criteria. Stunted children suffer from growth retardation caused by malnutrition resulting from inadequate dietary practices or frequent illnesses. SSGI data indicates that East Lombok Regency holds the third highest stunting rates in the NTB province. The knowledge possessed by caregivers correlates with the prevalence of stunting. This study seeks to ascertain the disparity in knowledge between households with stunted children and those with non-stunted children in Labuhan Haji Village, East Lombok. This study is an analytical observational research employing a cross-sectional methodology. 120 participants were chosen using sequential sampling for the data collection. Families with and without stunted children's knowledge of stunting was compared using the Kruskal-Wallis H test on SPSS. The study's findings indicate that families in Labuhan Haji Village, East Lombok, with stunted children and those without do not significantly differ in their understanding of stunting.